Amyloid in parenchymal organs in gelsolin (AGel) amyloidosis. (3rd July 2019) - Schmidt, Eeva-Kaisa; Kiuru-Enari, Sari; Atula, Sari; Tanskanen, Maarit
Abstract: Objectives: Previous clinical studies have shown frequent cardiac symptoms in patients with hereditary gelsolin (AGel) amyloidosis, possibly related to amyloid deposition in the heart and other internal organs. Previous studies on internal organ amyloid deposition in AGel amyloidosis have been based on small patient series. Methods: Paraffin-embedded tissue sections from 25 autopsied individuals (age at death 44.4–88.6 years) with AGel amyloidosis were stained with HE, Congo red and Herovici stains and immunohistochemistry against the low molecular weight gelsolin fraction was performed. The amount of amyloid was estimated semi-quantitatively. Results: AGel-based amyloid deposits were found in the myocardium and cardiac blood vessels in every patient. The deposits were mainly small and co-localized with regions with excess fibrosis in the myocardium. The lungs were positive for amyloid in 79%, renal parenchyma in 54% and renal blood vessels in 71% of the cases. The amount of myocardial, renal and hepatic amyloid correlated with age at death of the patients. Conclusions: We show the constant presence of AGel amyloid in the hearts of patients with AGel amyloidosis. Although the deposits were mainly small, the co-localization of amyloid with fibrosis may amplify the effect of pure amyloid deposition, possibly leading to clinical signs and symptoms.